APPLICATION OF NANOSTRUCTURES IN MICRO- AND OPTOELECTRONIC DEVICE ENGINEERING - Eshboltayev Iqbol Mamirjonovich; G‘ofurov Saidkamol Zokirjon ogli; Eshboltayev Ikromjon Iqbol ogli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper presents a scientific analysis of the application of nanostructures in the fields of microelectronics and optoelectronics. The operating principles of modern electronic and optical devices based on nano-scale structures, their advantages, and technological limitations are considered. The possibilities of enhancing device miniaturization, speed, and energy efficiency through the use of nanostructures are discussed.